2005
DOI: 10.1002/humu.20159
|View full text |Cite
|
Sign up to set email alerts
|

TCOF1 mutation database: Novel mutation in the alternatively spliced exon 6A and update in mutation nomenclature

Abstract: Recently, a novel exon was described in TCOF1 that, although alternatively spliced, is included in the major protein isoform. In addition, most published mutations in this gene do not conform to current mutation nomenclature guidelines. Given these observations, we developed an online database of TCOF1 mutations in which all the reported mutations are renamed according to standard recommendations and in reference to the genomic and novel cDNA reference sequences (www.genoma.ib.usp.br/TCOF1_database). We also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 29 publications
0
41
0
1
Order By: Relevance
“…Mutation Surveyor software (SoftGenetics, State College, Philadelphia, PA, USA) was used to identify sequence variants, and in silico splice prediction software used to predict alterations to splice sites (Alamut version 1.5 or 2.0, Interactive Biosoftware, Rouen, France). Nomenclature for sequence variants is in accordance with HGVS guidelines (www.hgvs.org) using GenBank NCBI reference sequence NM_001135243.1 (this includes exon 6A, but excludes exon 16A), as recommended by Splendore et al 14 …”
Section: Pcr and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation Surveyor software (SoftGenetics, State College, Philadelphia, PA, USA) was used to identify sequence variants, and in silico splice prediction software used to predict alterations to splice sites (Alamut version 1.5 or 2.0, Interactive Biosoftware, Rouen, France). Nomenclature for sequence variants is in accordance with HGVS guidelines (www.hgvs.org) using GenBank NCBI reference sequence NM_001135243.1 (this includes exon 6A, but excludes exon 16A), as recommended by Splendore et al 14 …”
Section: Pcr and Sequencingmentioning
confidence: 99%
“…The literature suggests that 62-82% of patients diagnosed with TCS have the diagnosis confirmed by sequence analysis of TCOF1, POLR1D or POLR1C, 1,2,12,13 however, the aetiology of the remainder remains uncertain. Gross deletions or other rearrangements of TCOF1 cannot be ruled out as they have only been investigated in one study by Splendore et al, 14 who found no alterations in seven patients. This study looks at a larger cohort of 182 subjects using sequencing and MLPA.…”
Section: Introductionmentioning
confidence: 99%
“…The mutation was named according to the genomic reference (NT_029289) and the cDNA that corresponds to the major treacle isoform (NM_001135243.1) [6]. Mutation nomenclature is based on Human Genome Variation Society (H.G.V.S.)…”
Section: Introductionmentioning
confidence: 99%
“…A reduction of the number of these cells at a critical time point early in embryogenesis leads to the cranial malformations typical for TCS [Dixon et al, 2007;Trainor, 2010]. In humans the phenotype shows a high inter-and intrafamilial variability ranging from mild, sometimes unaffected mutation carriers to severe forms leading to intrauterine death Splendore et al, 2002;Dixon et al, 2004;Teber et al, 2004;Masotti et al, 2005]. The spectrum of mutations within the TCOF1 gene that causes TCS is very heterogeneous The Treacher Collins Syndrome Collaborative et al, 1996;Splendore et al, 2002Splendore et al, , 2005So et al, 2004;Teber et al, 2004;Horiuchi et al, 2005;Dixon et al, 2007;Masotti et al, 2009].…”
mentioning
confidence: 99%
“…Lich /Prager /Lohmann /Wieczorek Mol Syndromol 2011;2:53-59 54 no causative mutation has been found so far [Splendore et al, 2000;Teber et al, 2004;Horiuchi et al, 2005;Masotti et al, 2005].…”
mentioning
confidence: 99%